THE COMPLEXITY IN ADOPTING NEW TECHNOLOGICAL PROGRAMS IN EDUCATION - Diana Tien Irafahmi (Universitas Negeri Malang, 2016)
Abstract: The Complexity in Adopting New Technological Programs in Education. The internet has become an increasingly important feature of the learning environment. For Indonesian university students, access to the internet has been provided in many campuses, including the Economics Faculty of the State University of Malang. As the installation of internet infrastructures in this Faculty is relatively new, it is interesting to investigate how and why students use such a new technology. This exploratory study refers to the notion of Activity Theory developed by Engeström. The primary intention is discussion of tensions as contradictions in an activity system. The findings indicate that the participants' attempts to use the internet in the Faculty were constrained by factors beyond participants' control. Using Activity Theory, this study has identified some contradictions that exist within the system. Abstrak: Kompleksitas Penggunaan Teknologi Baru dalam Pendidikan. Internet telah menjadi bagian penting dalam lingkungan pembelajaran. Bagi mahasiswa di Indonesia, akses terhadap internet telah disediakan di berbagai kampus, termasuk di Fakultas Ekonomi Universitas Negeri Malang. Berhubung instalasi infrastruktur internet di fakultas ini masih relatif baru, maka akan sangat menarik untuk meneliti mengapa dan bagaimana mahasiswa menggunakan internet di fakultas. Penelitian ini termasuk penelitian eksploratif yang menggunakan Teori Aktivitas (Activity Theory) rancangan Engestrom sebagai landasan teori. Fokus dari pembahasan berkisar pada "kontradiksi" yang terjadi dalam sistem aktivitas. Hasil penelitian menunjukkan bahwa usaha responden untuk menggunakan teknologi (internet) terhalangi oleh faktor-faktor di luar kontrol responden. Dengan menggunakan Teori Aktivitas, penelitian ini telah mengidentifikasi beberapa kontradiksi yang muncul dalam sistem penggunaan internet.